Implementation of master-slave method on multiprocessor-based embedded system: case study on mobile robot - Wajiansyah, Agusma; Purwadi, Hari; Astagani, Asrina; Supriadi, Supriadi (International Journal of Engineering and Technology, 2018)
In this research the master-slave method implemented on an embedded system using 3 processor applied to the mobile robot, to know the speed of program execution of robot. As a comparison is also used a robot with an embedded system based on single processor. From the experimental results, by applying the slave master method obtained the execution time of 546,5 Î¼s and the number of iteration 1079, while for single processor-based system obtained execution time average 67828 Î¼s and the amount of iteration average 147 times. Where the number of iterations is obtained by running the robot for 10 s. From this experiment, it can be concluded that there is a performance increase of 7.3% when compared to embedded systems based on single processor.Â